Radurization of carabeef - Sano, Ramon I. (1997)
This experiment was conducted to establish a methodology for the radurization of carabeef. Carabeef cuts were irradiated at the PARC in the frozen state and in carbon dioxide atmosphere to prevent off-flavors and off-odors. The different radiation dosages used were 0, 50, 75 and 100 krads. Low density polyethylene films were used as packaging materials and were heat sealed by candles. The irradiated samples were stored at 2±2°C. Storage study lasted for fifteen days. The index of spoilage used was microbial. Total plate count, yeast and mold count and Pseudomonas count were performed. Results revealed that the methods applied in the experiment were not effective in establishing an extension of shelf-life of carabeef. The main reason behind the failure was the occurence of post-radiation contamination of all the samples. This has resulted to a less in trend of the microbial loads of the meat cuts making the results unreliable. It was discovered however that carabeef is more durable and more resistant to deteriorative changes compared to beef
Thesis (B.S.)--University of the Philippines, Quezon City.
Typescript.
Keywords: Carabao meat; Meat -- Preservation